Industrial training report: Zheng Food (Malaysia) Sdn Bhd - Mohd Jamil, Izzati Syamimi (Universiti Teknologi MARA, Perlis, 2024)
Throughout my six-month internship at Zheng Food (Malaysia) Sdn Bhd, a halal dim sum producer, I had the opportunity to learn about applying concepts in the food industry. As a Finance major at UiTM, the course given me with hands-on experience that spanned the gap between theoretical knowledge and practical application in a dynamic food production scenario. As a Finance major at UiTM, the course given me with hands-on experience that spanned the gap between theoretical knowledge and practical application in a dynamic food production scenario. I used a PESTEL study to explore the factors determining Zheng Food, such as political stability, economic trends, consumer preferences, advances in technology, environmental restrictions, and legal framework. This analysis, combined with a SWOT analysis, revealed the company's strengths, weaknesses, opportunities, and threats. While it initially proved challenging to manage Zheng Foods systems, conquering this challenge helped me improve my thinking skills. In conclusion, this internship experience was genuinely transforming because it provided me with skills and motivated a desire to thrive in the food production profession after graduation.